Source distribution, ecological risks, and controlling factors of heavy metals in river sediments: Receptor model-based study in a transboundary river basin - Abu Reza Md Towfiqul Islam; Abu Hena Md Fazla Rabbi; Amit Hasan Anik; Rahat Khan; Md Abdullah Al Masud; Grara Nedjoud; Abubakr M. Idris; Md Naimur Rahman; Venkatramanan Senapathi (International Journal of Sediment Research, 2025)
In the context of transboundary rivers, which constitute intricate fluvial ecosystems, the persistent threat of heavy metals (HMs) contamination poses significant risks to ecosystem health. In this study, ecotoxicological hazards, governing factors, and the distribution of nine HMs (uranium (U), lead (Pb), cadmium (Cd), nickel (Ni), chromium (Cr), manganese (Mn), iron (Fe), zinc (Zn), and copper (Cu)), as well as sediment characteristics (sand, silt, clay, organic matter, and pH) are assessed within the sediment. The current investigation encompasses the analysis of twenty-seven sediment samples, utilizing inductively coupled plasma mass spectrometry, in the transboundary river basin of Bangladesh, specifically the Teesta River. Notably, the findings underscore the predominance of Cd as a contaminant, responsible for 51.85%, 81.84%, and 100% of the geo-accumulation index, contamination factor, and enrichment factor, respectively. The Teesta River emerges as moderately to highly polluted, with cumulative probabilities of 7.4%, 85.2%, and 7.4% denoting “medium”, “high”, and “priority” pollution levels, respectively. Regions in the upstream and downstream middle sections of the study area exhibit relatively higher pollution levels, particularly in proximity to Kaunia Upazila in the Rangpur district. Ecologically, the potential risk index indicates a low likelihood of ecological impacts at 77.8%, alongside a moderate risk observation of 22.2%. The current results attribute the distribution of these HMs to the pH and organic matter content within the sediment, serving as pivotal factors. To unravel the origins of the HMs, the positive matrix factorization (PMF) model successfully identifies four contributing factors, primarily from geogenic sources. Validation of the PMF model through Spearmen correlation and principal component analysis (PCA) reveals a consistent pattern, affirming its efficacy in this analysis. Within the region, HM sources are identified as originating from anthropogenic activities such as irrigation, industrial discharges, and domestic effluent, in addition to substantial inputs from geogenic sources. Recognizing the transboundary nature of metal pollution, the current study underscores the imperative for continuous and vigilant monitoring, coupled with the implementation of robust management practices. The interplay of both anthropogenic and geogenic factors necessitates a comprehensive approach to effectively and sustainably combat HM contamination.